The human brain intracerebral microvascular system: development and structure - Marín-Padilla, Miguel (Frontiers in Neuroanatomy, 2012)
The capillary from the meningeal inner pial lamella play a crucial role in the development and structural organization of the cerebral cortex extrinsic and intrinsic microvascular compartments. Only pial capillaries are capable of perforating through the cortex external glial limiting membrane (EGLM) to enter into the nervous tissue, although incapable of perforating the membrane to exit the brain. Circulatory dynamics and functional demands determine which capillaries become arterial and which capillaries become venous. The perforation of the cortex EGLM by pial capillaries is a complex process characterized by three fundamental stages: a) pial capillary contact with the EGLM with fusion of vascular and glial basal laminae at the contact site, b) endothelial cell filopodium penetration through the fussed laminae with the formation of a funnel between them that accompanies it into the nervous tissue while remaining open to the meningeal interstitium and, c) penetration of the whole capillary carrying the open funnel with it and establishing an extravascular Virchow-Robin Compartment (V-RC) that maintains the perforating vessel extrinsic (outside) the nervous tissue through its entire length. The V-RC is walled internally by the vascular basal lamina and externally by the basal lamina of joined glial cells endfeet. The VRC outer glial wall appear as an extension of the cortex superficial EGLM. All the perforating vessels within the V-RCs constitute the cerebral cortex extrinsic microvascular compartment. These perforating vessels are the only one capable of responding to inflammatory insults. The V-RC remains open (for life) to the meningeal interstitium permitting the exchanges of fluid and of cells between brain and meninges. The V-RC function as the brain sole drainage (prelymphatic) system in both physiological as well as pathological situations.